Financial Assistance from Arab Countries and Arab Regional Institutions - van den Boogaerde, P. (Occasional Papers; Occasional Paper ;, 1991)
Arab financial assistance to developing - particularly Arab - countries rose sharply between 1973 and 1980 but fell gradually through the 1980s, owing mainly to weakening oil prices. As a percent of GNP, however, Arab contributions remain the largest among major donors. This paper surveys the volume and distribution of Arab financing from 1973 to 1989.